Islam, Demokrasi, dan Institusi Politik di Indonesia, Turki, dan Dunia Islam - Saputra, Rangga Eka (Studia Islamika, 2017)
Edward Schneier. 2016. Muslim Democracy: Politics, Religion and Society in Indonesia, Turkey and the Islamic World. New York: Routledge.This book is one of the most recent and pivotal works in studying of democratization in Muslim world. The controversial inference from the Edward Schneier’s work is that the variable of religion, especially Islam in this context, is not appropriate enough to explain the success or failure of democracy in Muslim majority countries. By using the mix method of statistics comparison and comparative case studies in Indonesia and Turkey, he argues that the difference of colonialization, history, geopolitics and the growth of developmental economy is crucial variable to elucidate the different outcome of democratization in Muslim countries. However, this book is like a generalization from prior works regarding this topic especially in explaining Islam and democracy in both countries. Some arguments fell down repeatedly with prior scholars such as the explanation of civil Islam to explain Indonesia democratization and the role of military-Islamist relations in depicting democratization in Turkey.DOI: 10.15408/sdi.v24i1.5223